Investigating the Influence of Processing Conditions on Dissolution and Physical Stability of Solid Dispersions with Fenofibrate and Mesoporous Silica - Ana Baumgartner; Nina Dobaj; Odon Planinšek (MDPI AG, 2024)
The study aimed to enhance the solubility of the poorly water-soluble drug, fenofibrate, by loading it onto mesoporous silica, forming amorphous solid dispersions. Solid dispersions with 30% fenofibrate were prepared using the solvent evaporation method with three solvents (ethyl acetate, acetone, and isopropanol) at different temperatures (40 °C, boiling point temperature). Various characteristics, including solid-state properties, particle morphology, and drug release, were evaluated by different methods and compared to a pure drug and a physical mixture of fenofibrate and silica. Results revealed that higher solvent temperatures facilitated complete amorphization and rapid drug release, with solvent choice having a lesser impact. The optimal conditions for preparation were identified as ethyl acetate at boiling point temperature. Solid dispersions with different fenofibrate amounts (20%, 25%, 35%) were prepared under these conditions. All formulations were fully amorphous, and their dissolution profiles were comparable to the formulation with 30% fenofibrate. Stability assessments after 8 weeks at 40 °C and 75% relative humidity indicated that formulations prepared with ethyl acetate and at 40 °C were physically stable. Interestingly, some formulations showed improved dissolution profiles compared to initial tests. In conclusion, mesoporous silica-based solid dispersions effectively improved fenofibrate dissolution and demonstrated good physical stability if prepared under appropriate conditions.